Endometrial Cancer Type 2 Incidence and Survival Disparities Within Subsets of the US Black Population - Pinheiro, Paulo S.; Medina, Heidy N.; Koru-Sengul, Tulay; Qiao, Baozhen; Schymura, Maria; Kobetz, Erin N.; Schlumbrecht, Matthew P. (Frontiers in Oncology, 2021)
Introduction Endometrial cancer type 2 (EC2) carries a worse prognosis compared to EC type 1. EC2 disproportionately affects Black women among whom incidence is higher and survival is poorer compared to Whites. Here we assessed EC2 incidence and survival patterns among US Black ethnic groups: US-born Blacks (UBB), Caribbean-born Blacks (CBB), and Black Hispanics (BH). Methods We analyzed population-based data (n=24,387) for the entire states of Florida and New York (2005–2016). Hysterectomy-corrected EC2 incidence rates were computed by racial-ethnic group, and survival disparities were examined using Cox regression adjusting for tumor characteristics, poverty level, and insurance status. Results EC2 incidence rates were highest among UBB (24.4 per 100,000), followed by CBB (18.2), Whites (11.1), and Hispanics of all races (10.1). Compared to Whites, the age-adjusted cause-specific survival was worse for non-Hispanic Blacks (aHR: 1.61; 95%CI 1.52–1.71) and Hispanics of all races (aHR:1.09; 95% CI:1.01–1.18). In relation to Whites, survival was worse for non-Hispanic Blacks: UBB (aHR:1.62; 95%CI 1.52–1.74) and CBB (aHR:1.59; 95% CI:1.44–1.76) than for BH (aHR:1.30; 95% CI:1.05–1.61). Surgical resection was associated with a lower risk of death, while carcinosarcoma subtype and advanced stage at diagnosis were associated with a greater risk. Conclusions Although higher EC2 incidence and lower survival are observed among all African-descent groups, there are significant intra-racial differences among UBB, CBB, and BH. This heterogeneity in EC2 patterns among Black populations suggests an interplay between genetic and socioenvironmental factors.